Secondary hip dysplasia increases risk for early coxarthritis after Legg-Calve-Perthes disease. A study of 255 hips. Issue 14 (26th October 2019) - Moličnik, Andrej; Janša, Jošt; Kocjančič, Boštjan; Kralj-Iglič, Veronika; Dolinar, Drago
Abstract: The biomechanical parameters of the hip joint articular surface were analysed in 141 adult hips after Legg-Calve Perthes Disease, and 114 contralateral unaffected hips (controls), by using HIPSTRESS mathematical models. Geometrical parameters, assessed from anteroposterior and axial radiograms, were used as input to models for resultant hip force and contact hip stress. Results confirm previous indications that head enlargement after the Legg-Calve-Perthes Disease compensates the values of hip stress. Furthermore, it was found that an increased risk for coxarthritis development after the disease is secondary to concomitant hip dysplasia, with considerable and statistically significantly lower centre-edge angle and unfavourable distribution of stress.